2012
DOI: 10.1182/blood-2011-01-327619
|View full text |Cite
|
Sign up to set email alerts
|

Sequential mutations in Notch1, Fbxw7, and Tp53 in radiation-induced mouse thymic lymphomas

Abstract: T-cell acute lymphoblastic lymphomas commonly demonstrate activating Notch1 mutations as well as mutations or deletions in Fbxw7. However, because Fbxw7 targets Notch1 for degradation, genetic alterations in these genes are expected to be mutually exclusive events in lymphomagenesis. Previously, by using a radiationinduced Tp53-deficient mouse model for T-cell acute lymphoblastic lymphoma, we reported that loss of heterozygosity at the Fbxw7 locus occurs frequently in a Tp53-dependent manner. In the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Inactivating mutations of FBXW7 , reported in about 20% of T‐ALL patients (Mansour et al , ; Kox et al , ; Zuurbier et al , ; Jenkinson et al , ), result in the inability of FBXW7 to bind the NOTCH1 PEST domain to perform proteolytic cleavage function, thereby increasing the half‐life of the ICN. Furthermore, reduction of FBXW7 activity could also play a role in the development of the disease (Jen et al , ). Therefore, many studies have investigated the impact of mutations of both FBXW7 and NOTCH1 on treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivating mutations of FBXW7 , reported in about 20% of T‐ALL patients (Mansour et al , ; Kox et al , ; Zuurbier et al , ; Jenkinson et al , ), result in the inability of FBXW7 to bind the NOTCH1 PEST domain to perform proteolytic cleavage function, thereby increasing the half‐life of the ICN. Furthermore, reduction of FBXW7 activity could also play a role in the development of the disease (Jen et al , ). Therefore, many studies have investigated the impact of mutations of both FBXW7 and NOTCH1 on treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Protein coding regions were amplified by PCR from tumour cDNA using primers to produce a single amplicon from the Pten and Trp53 genes and several overlapping fragments from the Ikzf1 gene. For Notch1 , primers flanking the HD domain and flanking the PEST domain were used to amplify these two regions known to harbour the majority of Notch1 activating mutations [ 28 ]. PCR amplicons were isolated by excising bands after agarose gel electrophoresis, which were then purified and subjected to direct DNA sequencing using the original PCR primers and in some cases, additional internal primers.…”
Section: Methodsmentioning
confidence: 99%
“…21 Mutations in the NOTCH1 PEST domain and FBXW7 in the same patient are infrequent, and a mouse model of radiation-induced T-cell acute lymphoblastic lymphomas has shown that reduced Fbxw7 activity precludes the requirement for Notch1 PEST domain mutations for tumor development. 22 However, co-incident NOTCH1 HD domain and FBXW7 mutations do occur and, as with NOTCH1 HD and PEST domain mutations, act in synergy. 19,21,23 Several studies investigating the prognostic significance of NOTCH1 and FBXW7 mutations in pediatric T-ALL have been published.…”
Section: Introductionmentioning
confidence: 99%